Nurse‐led standardized intervention for low anterior resection syndrome. A population‐based pilot study. (9th February 2021) - Dalsgaard, Peter; Emmertsen, Katrine Jøssing; Mekhael, Mira; Laurberg, Søren; Christensen, Peter
Abstract: Aim: Our aim was to study the implementation of the low anterior resection syndrome (LARS) score in a clinical setting and to evaluate a nurse‐led standardized intervention for bowel dysfunction following rectal cancer surgery. Method: All patients who underwent curatively intended, restorative rectal cancer resection in a single centre between 2012 and 2016 were screened using the LARS score. At clinical follow‐up, patients with major LARS were offered treatment in a nurse‐led clinic. Data were retrospectively collected from patients' electronic medical records. Results: In total, 190 out of 286 (66%) patients were screened with the LARS score of whom 89 had major LARS. A total of 86 patients requested treatment for their bowel dysfunction and the majority obtained acceptable function after nurse‐led optimized conservative treatment. Seventeen patients went on to transanal irrigation, and seven patients were treated with biofeedback. Five patients were referred for surgery, three for gastroenterological evaluation. After treatment in the clinic, patients achieved a statistically significant decrease in median LARS score from 37 (interquartile range 34–39) to 31 (interquartile range 23–34) ( P < 0.001), and the prevalence of major LARS fell from 95% to 53% ( P < 0.001). Conclusion: Screening for LARS was not optimal as one‐third of patients were not screened. The majority of patients with major LARS requested treatment for their symptoms and could be successfully treated with standardized interventions managed in a nurse‐led setting.